Toward understanding the dimensional crossover of canonical spin-glass thin films - Zhai, Qiang; Orbach, Raymond L. (Frontiers in Physics, 2024)
Spin-glass thin films exhibit many features different from the bulk. The freezing temperatures of spin-glass films are suppressed for reduced thickness and follow the Kenning relation.The dynamics are altered near the vacuum interface. These phenomena are closely related to the lower critical dimension of spin glasses, the spin-glass correlation length and the dimensional crossover from d=3 to d=2. In this article, we review the experimental facts and theoretical perspectives for spin-glass thin films. We focus on canonical spin-glass systems with the Ruderman-Kittel-Kasuya-Yosida (RKKY) interaction between magnetic impurities in a nonmagnetic host. Open questions to be addressed are emphasized.